Developing a Cheaper, Longer-lasting Way to Track Cocoa's Most Costly Pest, The Cocoa Pod Borer, Conopomorpha cramerella (Lepidoptera: Gracillariidae) - Niogret, Jerome; Tabanca, Nurhayat; Zhang, Aijun (Universitas Gadjah Mada, 2025)
N/A